A Life Table of the Asiatic Maize Stem Borer, Ostrinia furnacalis Guene - Hussein, Mohd Yusof; Ibrahim, M. B. (1992)
The survivor ship and fecundity rates of Ostrinia furnacalis Guenee were measured in the laboratory using the major host plant, the maize plant. Raw data analysis of the age-specific single-sex female life table is described. The intrinsic rates of increase were calculated with respect to single sex. Using the single-sex method, the intrinsic rate of natural increase (1), the net reproductive rate (R), the generation time (T) and the doubling time (DT) were 0.157, 139.6, 31.5 days and 4.62 days, respectively. The age-specific survival and fecundity curves showed that ovi position peakedon the 8th day after female emergence and lasted for 11 days. The survival rates for the egg, larval and pupal stages were 96, 85 and 90%, respectively. The maximum life span (from egg to death of adult) was 38 days. The male moth emerged 2 days earlier than the females. Adult longevity averaged 7 days. Female fecundity reached a maximum of 115 eggs with an average fecundity of 60 eggs per female